ACTIVE LEARNING AND INCLUSION AGENTS: A NECESSARY TRAINING (RevistAleph, 2021)
Abstract Who are the workers called “inclusion-support-agents” in Brazil? Based on a literature review we applied a questionnaire to learn about the personal and professional profiles of these workers. The questionnaire was applied to pre- and in-service school inclusion-support-agents from a state and a federal school in Rio de Janeiro. The results pointed the need of investment in training, given the challenges faced by special education in the inclusive perspective, combining innovative technologies and diversity of learning. In conclusion, the adequate training in active learning methodologies of these professionals will help provide real learning and socialization scenarios of students with Special Educational Needs and allow schools and universities to fully achieve their educational objectives.Keyword: continuing education, agent support for school inclusion, active learning.